Choice of representative period of observations of soil water regime under crops - Tkachuk, Andrij; Ткачук, Андрій Васильович; Zaporozhchenko, Viktoriia; Запорожченко, Вікторія Юріївна; Tkachuk, Tetyana; Ткачук, Тетяна Іванівна (Springer Science+Business Media, 2024)
We consider various methods of determining the representative period of observations for developing irrigation regimes: integrated difference curves, calculation of soil moisture reserves of different repeatability by a series of observations of different duration, and analysis of deviations of average values over different periods up to the entire growing season. Розглянуто різні методи визначення репрезентативного періоду спостережень для розробки режимів зрошення: інтегральні різницеві криві, розрахунок запасів вологи в ґрунті різної повторюваності за рядом спостережень різної тривалості, аналіз відхилень середніх значень за різні періоди вегетаційні періоди.
Вибір репрезентативного періоду спостережень за водним режимом ґрунту посівів
Keywords: Soil moisture reserves; Запаси вологи в ґрунті; dynamics; динаміка; irrigation regime; режим поливу